Designing an Information System for Student Admissions at SMAN 1 Pademawu Using the Waterfall Method - Fauzan Prasetyo Eka Putra; Fadilatul Mu'minin; Alief Nuraini; Selviana Nur Rizqi Barokah; Khairurrozi Khairurrozi (Brilliance: Research of Artificial Intelligence, 2025)
New Learner Admission (PPDB) is one of the processes of accepting students at every school level, starting from PAUD, kindergarten, elementary school, junior high school, to high school / vocational school. This term is used by various school bodies when they want to accept new students. Often these institutions experience problems in managing the administration of new participants, one of which is SMAN 1 Pademawu. The obstacles that occur include the buildup of queues of participants who register at the institution and constraints in inputting new participant data due to the limited number of PPDB organizing committee members. Therefore, this research will create a PPDB information system to overcome the obstacles experienced by the institution. The information system created is in the form of flow chart design, ERD (Entity Relationship Diagram), UML (Unified Modeling Language) and DFD (Data Flow Diagram). Using Javascript programming language, React Js framework and bootstrap. The result of this research is the construction of PPDB information system at SMAN 1 Pademawu by using waterfall method. With this system, it is expected to facilitate the PPDB committee of SMAN 1 Pademawu in managing or inputting data and reducing the buildup of registration queues effectively and efficiently.